The role of digital communication in introducing public relations objectives in economic institutions - علی, م. شوخان أبو بكر علي; محمد, م.م. چنور احمد محمد (Sulaimani Journal for Humanities, 2025)
Communication within an organization is considered to be one of the most important activities, in the absence of communication, an organization is not likely to reach its goals, digital communication is one of the main axes for exchanging information and ideas within an organization, it is one of the main routs of modern communication, and it has a role in changing our methods of communication and interactions with others. One of the critical problems that stems from this subject is, to what extent has digital communication played a role in introducing the goals of public relations in industrial organizations. In the regards of reaching a goal in this research, descriptive method is used along with survey forms. Asiacell has been used as sample research, Asiacell company has been selected as a chosen sample for the research to reach the required goal. The main goals the research has achieved: - One of the most important services that digital communication has offered is the betterment of sharing information and news, along with the fact that the speed and simplicity of digital communication plays a role in being aware and analyzing information. - Digital information has had a pivotal role in achieving the goals and benefits of the organization. - Digital communication has had a role in improving employee efficiency. - The methods of communication between employees commenced with phone calls and then was transformed to emails. - Digital Communication has played a role in motivating the employees to have a positive image on the organization in the perspective of the employees. - The rapport between the main goals of the organization and public relation is seen in the explanations of the policies of the organization, the rules and guidelines of work and achieving a mutual understanding between the employees and management staff of the organization.
Keywords: Digital Communication; Public Relations; Public Relations Objectives; Economic Institutionalization